Indigenous voices in the State Library of New South Wales*. Issue 1 (2nd January 2016) - Thorpe, Kirsten; Byrne, Alex
Abstract: The State Library of New South Wales holds the world's most extensive collection on the European exploration and colonisation of Australia and its region and the subsequent development of Australia. Much is held about the Indigenous peoples, some created by Indigenous artists and chroniclers, but the majority by others including explorers, government officers, missionaries and settlers as well as the more recent ethnographers, historians and writers. Many of the records are fragmentary and hidden within documents dealing with other matters. The State Library is working to make these records available in consultation with Indigenous communities. It also seeks to include more and stronger Indigenous voices to reflect on Indigenous experience and provide commentary on the material in the Library's collections. The Library's partnership with the New South Wales public library network offers a means for engagement with communities as well as an opportunity to provide better services to Indigenous people.